Transverse versus vertical incision approach in elective ventral hernia repair - A comparative study - Renganathan M; Mukesh Kumar P; Sathyaraj P; Amanyu T; Jemin Bharath R (Asian Journal of Medical Sciences, 2023)
Background: Ventral hernias are commonly associated with not infrequent complications and significant recurrence rates, often resulting in future procedures. The relative merits and disadvantages of vertical versus transverse incisions remain subjects of active debate. Aims and Objectives: The study aims to compare the relative merits, demerits, and outcomes between patients of ventral hernia who have undergone open mesh repair through a transverse incision and a vertical incision. Materials and Methods: In this prospective study, 100 patients were admitted to Government Rajaji Hospital for ventral hernia repair and those satisfying the inclusion criteria were divided into two groups, A and B, 50 each. In group A, open mesh repair was done through a transverse incision; in group B, open mesh repair was done via a vertical incision. The study compared the incidence of surgical site infection (SSI), flap necrosis, wound dehiscence, pain, and mean hospital stay. Results: On comparing the groups, it has been seen that the incidence of significant pain (taken as a visual analog scale score of 3.5 or more) was 16% in group A (transverse incision) compared to 34% in group B (vertical incision), which is statistically significant. The incidence of SSI, flap necrosis, wound dehiscence, and mean hospital stay were more or less the same and statistically insignificant. Conclusion: The group in which a transverse incision was used for ventral hernia repair showed significantly less post-operative pain than the group in which a vertical incision was used. Hence, the use of transverse incision in elective open mesh repair for ventral hernias should be considered.